"Break and Be Broken", She Said, "That is the Law of Life": Loss and Racial Melancholia in Marlene van Niekerk's Agaat*. Issue 3 (2nd July 2016) - Demir, Danyela
Summary: Yvette Christiansë (2003: 373) argues that the Truth and Reconciliation Commission neglected daily narratives of loss in favour of an attempt of a nationwide process of mourning and a subsequent closure of the apartheid past. One account of quotidian losses certainly is Marlene van Niekerk's novel Agaat (2004), which focuses on the relationship between the white farm owner Milla and her coloured servant Agaat. Throughout the story, Milla attempts to turn Agaat into a "refined" coloured, maintain control over her body and sexuality. This alienation leads to losses on Milla's part, especially the emotional loss of a potential mother-daughter bond. Because the story is told from Milla's perspective, Agaat's voice is largely silenced. It has often been noted that Agaat uses mimicry in order to subvert Milla's rule. However, critics have largely overlooked Agaat's discriminatory behaviour towards the other coloured farm workers. By drawing on Anne Cheng's concept of racial melancholia, I argue that this behaviour can be seen as Agaat's attempt of melancholically repressing a part of her coloured identity which she has to negate in order to gain acceptance by Milla. The latter's melancholia manifests through the incorporation of Agaat as her lost object of love and the simultaneous rejection of Agaat's racialised body.